PENGEMBANGAN SOAL MATEMATIKA MODEL PISA pada KONTEN UNCERTAINTY AND DATA untuk MENGUKUR KEMAMPUAN PENALARAN MATEMATIS SISWA SMP - Siti Asyah; Elya Rosalina; As Elly (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2019)
This study aims to produce a Mathematical Problem based on the PISA Model in measuring the level of mathematical reasoning ability in valid and practical SMP 1 students and looking at the mathematical reasoning abilities of students in solving the mathematical problems of the PISA model on uncertainty and data content. This research is a development research with ADDIE development model. This model consists of five stages of development, namely Analysis, Design, Development, Implementation and Evaluation. Products developed in this study are in the form of PISA questions on statistical material and opportunities. From the results of the research carried out by the researcher obtained: (1) the validity of a question indicates that the question depends on the feasibility category such as the developed question obtaining good results in the feasibility component of language by obtaining a mean score of 3.16, on the material feasibility get a good category with an average score of 3.22, then in the construct feasibility category get a very good predicate with a mean score of 3.85. So that the average score obtained by the three experts is 3.35 and is categorized very well. (2) the quality of the question is viewed from various aspects such as practicality which are classified as "Good" with an average score of 3.43 then after that can be determined through the response results assessed by students regarding mathematical problems based on PISA models for uncertainty and data content so that they can measure students' mathematical reasoning abilities. For mathematical reasoning abilities in students using mathematical questions based on the PISA model get an average score of 2.19 categorized quite well.